Peningkatan Pengetahuan Siswa SMK dalam Menjalankan Pola Hidup Sehat Untuk Mencegah Berbagai Gangguan Kesehatan - Sukarmin Sukarmin; Islami; Muh.Abdul Rozaq (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
There are about 360 million adolescents in the world and about 20% are in the countries of the Southeast Asian region. The transition from childhood to adulthood involves dramatic changes in physical, sexual, psychological and social development, all occurring at the same time. Many health problems that arise in adolescents come from patterns and lifestyles that are less supportive of health. Lifestyles such as smoking, low-fiber diets, lack of exercise and insufficient rest time are problems experienced by many adolescents. One of the main factors that support poor lifestyle patterns is the lack of knowledge of adolescents. The results of the initial evaluation of 31 adolescents of SMK Muhammadiyah Pesantren in Kudus using 20 knowledge questionnaires about lifestyle found that 21 (67.8%) students had less knowledge of lifestyle patterns, 5 (16.1%) students had moderate knowledge and 5 (16.1%) students had good knowledge. Providing education is one method to increase adolescent knowledge in improving better lifestyle patterns. Health Education Engineering goes through the opening, implementation, evaluation and closing stages that last for 100 minutes. The evaluation results found that 8 (25.8%) students had less knowledge of lifestyle patterns, 11 (35.5) students had moderate knowledge and 12 (38.7%) had good knowledge. The provision of health education can increase adolescent knowledge in improving good lifestyle patterns to prevent various health problems in adolescents.